Continuous dewatering of sludge and aqueous slurries by sodium polyacrylate - Osei Asafu-Adjaye; Brian Via; Bhima Sastri; Sujit Banerjee (Case Studies in Chemical and Environmental Engineering, 2023)
Aqueous slurries such as sludge are typically dewatered thermally or through compressive systems such as presses or centrifuges. A new approach to dewatering these slurries is presented and validated. A dilute suspension of sodium polyacrylate (a superabsorbent polymer) in water was pumped through a soaker hose (typically used for irrigation) immersed in the aqueous slurry to be dewatered. Water from the slurry entered the hose through its pores and was absorbed by the acrylate and then continuously pumped out. In the best case the polyacrylate removed 38 times its own weight in water. The soaker hose was used in a reverse configuration, i.e. instead of delivering water to its surroundings, it passively absorbed water from its surroundings and trapped it in the polyacrylate. The spent polyacrylate was subsequently dewatered with supercritical CO2, which displaced the water non-evaporatively from the polymer. The process was illustrated by continuously dewatering alum sludge. Sludge ponds can be potentially dewatered in situ without dredging.